2010
DOI: 10.1007/s11803-010-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

2.5D scattering of incident plane SV waves by a canyon in layered half-space

Abstract: This paper presents a 2.5D scattering of incident plane SV waves by a canyon in a layered half-space by using the indirect boundary element method (IBEM). A free fi eld response analysis is performed to provide the displacements and stresses on the boundary of the canyon where fi ctitious uniform moving loads are applied to calculate the Green's functions for the displacements and stresses. The amplitudes of the loads are determined by the boundary conditions. The free fi eld displacements are added to the fi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure 10, a 3D semicylindrical canyon (radius r=100 m) lies in a two‐layered half‐space, and subjected to obliquely incident SV wave with θv=30 and θh=45. In this study, we adopted the solutions obtained using the IBEM from Ba and Liang [ 16 ] for comparisons. Please note that the original problem is an infinite long canyon.…”
Section: Verification and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 10, a 3D semicylindrical canyon (radius r=100 m) lies in a two‐layered half‐space, and subjected to obliquely incident SV wave with θv=30 and θh=45. In this study, we adopted the solutions obtained using the IBEM from Ba and Liang [ 16 ] for comparisons. Please note that the original problem is an infinite long canyon.…”
Section: Verification and Validationmentioning
confidence: 99%
“…Luco et al [12] and Luco and de Barros [3] investigated the 3D response of cylindrical canyon and valley in a layered half-space subjected to obliquely incident P, SV, and SH waves. Later the same problems were solved using direct [13,14] boundary element method (BEM) and indirect boundary element method [15,16] (IBEM). Bielak et al [17] utilized a local second-order impedance element to simulate the seismic SH wave propagation, which accounted for oblique incidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that there are significant differences between 3D scattering and 2D scattering [39,40]. In recent years, some scholars have begun to study the 2.5D model [41][42][43][44][45], which has been used to respond to three-dimensional ground motion. However, the 2.5D model still assumes that the valley section is the same and that there is no spatial change in the terrain.…”
Section: Introductionmentioning
confidence: 99%